2005
DOI: 10.1080/09064700500307201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fructo-oligosaccharide on villous height and disaccharidase activity of the small intestine, pH, VFA and ammonia concentrations in the large intestine of weaned pigs

Abstract: An experiment was conducted to investigate changes in the lumen and wall of the intestinal tract of weaned pigs caused by fructo-oligosaccharides (FOS) and consequences for growth. Twelve male pigs weaned at 24 days were individually housed and fed either control, 0.25% FOS, or 3% FOS diets for 21 days after weaning. The pH of chyme in the caecum and proximal colon were lower (p B/0.001) in 3% FOS compared to other treatments. Mean molar proportions (%) of total SCFA values along the large intestine were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
2
10
0
1
Order By: Relevance
“…The rectal pH in piglets that were slaughtered at weaning was not different from that in piglets that were fed with maltodextrin. The absence of an effect (P > 0.05) from the use of FOSs on the pH of the organs that were evaluated (Table 4) confirms the results obtained by Shim, Williams and Verstegen (2005), who did not observe an effect of using 0.25% FOSs in the diet on the pH values of the gastrointestinal tract; however, when they used 3.0% FOSs in the diet, they did observe a reduction in the proximal colon pH, because there was higher short-chain fatty acid production (above the absorption capacity of the large intestine).…”
Section: Experiments IIsupporting
confidence: 83%
See 1 more Smart Citation
“…The rectal pH in piglets that were slaughtered at weaning was not different from that in piglets that were fed with maltodextrin. The absence of an effect (P > 0.05) from the use of FOSs on the pH of the organs that were evaluated (Table 4) confirms the results obtained by Shim, Williams and Verstegen (2005), who did not observe an effect of using 0.25% FOSs in the diet on the pH values of the gastrointestinal tract; however, when they used 3.0% FOSs in the diet, they did observe a reduction in the proximal colon pH, because there was higher short-chain fatty acid production (above the absorption capacity of the large intestine).…”
Section: Experiments IIsupporting
confidence: 83%
“…Before the start of the experiment, the facilities were properly cleaned, disinfected, and subjected to fallowing for a minimum of 15 d. Moreover, the pre-starter feeds contained zinc oxide, which is proven to be effective in reducing E. coli adhesion to the intestinal cells (SARGEANT et al, 2010), thereby reducing enteric problems in weaned piglets. Nemcová et al (1999) and Bomba et al (2002) observed the beneficial effect of using FOSs in the diets of piglets on the intestinal microflora, which, according to Shim, Williams and Verstegen (2005), might induce an increase in feed intake because of a reduction in digestive disorders.…”
Section: Experiments Imentioning
confidence: 99%
“…In piglets fed prebiotics, probiotics or synbiotics (a combination of the two) the population of bifidobacteria in the ileum increased and prebiotics and synbiotics increased their body weight gain (Shim et al, 2005). The dietary combination of probiotics and Biomannan oligosaccharides improved the feed conversion ratio in broiler vaccinated against coccidiosis (Sun et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It could then be hypothesized that prebiotic intervention would increase piglet resilience against infection by competitive inhibition of pathogenic bacteria or general improvement of health status. Studies in animals have, however, not been conclusive in establishing if the same effect is possible in weaning piglets (13)(14)(15)(16)(17), perhaps because of difficulties in observing an effect in a healthy animal. In contrast, studies using experimental infections along with prebiotic intervention generally show a protective effect against PWD (18)(19)(20).…”
mentioning
confidence: 99%